IMPROVING THE COMPETENCE AND QUALITY OF HUMAN RESOURCES IN THE HOSPITALITY SECTOR: A PERSPECTIVE OF HOTEL ENTREPRENEURS IN KENDARI - Wardiningsih, Harpiang; Mokodompit, Eliyanti Agus (Penelitian dan Pengembangan Ilmu, 2024)
The hospitality industry in Indonesia, particularly in Kendari, faces challenges in improving the competence and quality of human resources (HR) in line with the rapid growth of the tourism sector. Although hotel managers recognize the importance of employee training, the skills gap between the workforce's existing competencies and the growing demands of the hospitality industry remains a significant issue. This study addresses the knowledge gap regarding HR development challenges in Kendari's hospitality sector, caused by the mismatch between available training programs and the practical competencies required in the field. This research adopts a descriptive qualitative approach, conducting in-depth interviews with hotel owners, HR managers, employees, academics, and government representatives to analyze the problems and training needs in the hospitality industry. The findings contribute significantly to the development of human resource management theory in the hospitality sector, as well as providing insights for hotel managers and local governments to design more relevant training policies based on market needs.